Study of drying and extraction of mint essential oil (Mentha arvensis L.) (Research, Society and Development, 2022)
The species Mentha arvensis L., popularly known as Japanese mint, produces the essential oil rich in menthol, whose applications in the pharmaceutical, food and cosmetic industries give it great socioeconomic expression. The objective of this work was to study the drying and oil extraction of Japanese mint. The Japanese mint was harvested in humid and hot weather, with the beginning of flowering, correctly packaged and submitted to drying in an oven at two temperatures, 40 °C and 60 °C. The humidity of the samples found was 86.73 %. Then the drying curves were obtained at the two temperatures and it was determined that the drying model that best fitted the experiment was the Peleg model. After drying, the two fractions were milled separately in a knife mill, then the Sauter diameter was determined at 40 °C: 0.237 mm and 60 °C: 0.250 mm. After determining the Sauter diameter, exhaustive oil extraction was performed in a Soxhlet apparatus using n-hexane as extracting solvent with the samples retained on 70 and 100 mesh sieves with diameters of 0.150 and 0.215 mm for the samples dried at temperatures of 40 °C and 60 °C, as they were the sieves that obtained the highest redite mass of dehydrated Japanese mint. The oil extraction yield from the dry fraction at 60 °C showed better yield in the studied diameters, obtaining. 3.74 % essential oil extraction yield. Observing the extraction yield in relation to the diameter of the samples, the diameter of 0.180 mm was better at different temperatures. Where it can be concluded that the temperature and diameter of the Japanese mint particles influence the yield of essential oil extraction.